Sakralitas Burung Enggang dalam Teologi Lokal Masyarakat Dayak Kanayatn - Claudya Ingrid Sahertian (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2021)
This article aims to explore the culture of the Dayak Kanayatn people regarding the rituals and sacredness of hornbills. Retrieval of data using qualitative research with the ethnography method, through interview techniques, observation, documentary studies, and literature studies. The community makes hornbills a sacred symbol. This attitude can be seen when the community carries out Karana traditional rituals as an implementation of local theology and narrates them in dances, carvings, carvings, and traditional clothing attributes. Through rituals, the community believes that the hornbill is a link between heaven (subayatn) and the world that brings people to death (pidara) into eternity. Hornbills have a significant influence on the Kanayatn Dayak indigenous people because they contain noble values. Everything related to hornbills, including their lifestyle, natural seed dispersers, forest guards, physical beauty, has become sacred to the Kanayatn Dayak community. This study concludes that the hornbill is a sacred symbol in local theology and capital of social integration for the Kanayatn Dayak community.AbstrakArtikel ini bertujuan untuk mengeksplorasi budaya masyarakat Dayak Kanayatn tentang ritual dan sakralitas burung Enggang. Pengambilan data menggunakan penelitian kualitatif dengan metode ethnografi dan nethnografi, melalui teknik wawancara, observasi, studi dokumenter dan studi pustaka. Masyarakat menjadikan burung Enggang sebagai simbol sakral. Sikap tersebut terlihat ketika masyarakat melaksanakan ritual adat Karana sebagai implementasi teologi lokal, serta menarasikannya dalam tarian, ukiran, pahatan dan atribut pakaian adat. Melalui ritual  masyarakat meyakini bahwa burung Enggang sebagai penghubung  surga (subayatn) dan dunia. Burung Enggang yang membawa orang meninggal (pidara) masuk kekekalan. Burung Enggang memberi pengaruh yang signifikan bagi masyarakat adat Dayak Kanayatn karena mengandung nilai-nilai yang luhur. Segala sesuatu yang berhubungan dengan burung Enggang baik pola hidup,  pemencar biji alami, penjaga hutan, keindahan fisik, menjadi sakral bagi masyarkat Dayak Kanayatn. Penelitian ini menyimpulkan bahwa Burung Enggang adalah simbol sakral dalam teologi lokal  dan modal integrasi sosial bagi masyarakat Dayak Kanayatn.